(untitled) (Analele Universității București. Limba și literatură română, 2024)
This article aims to explore some possible connections between the ancient myth of Ariadne and folk narratives of later periods. To this end, it adopts a perspective based on the types and motifs approach, by employing essential tools used in contemporary folkloric research, such as Uther 2004 and Thompson 1955-1958. It starts by discussing the usefulness and limitations of this approach when it comes to comparisons between folklore and antiquity and continues with the analysis of a rather peculiar Romanian fairy tale, the only one registered in Romania as containing the motif “R121.5 Ariadne’s Thread”. The singularity of this text in the Romanian folk culture is met by an equal distinctiveness when confronted with other ancient and modern narratives containing the action of traversing a labyrinth by means of a thread. Therefore, this Romanian fairy tale provides us with the opportunity to draw attention to some of the inconsistencies present in the typological approach commonly adopted by some recent studies dedicated to folklore in the ancient world. However, if we managed to resolve some of the problems inherent in the concept of type, the search for motivic similarities could stimulate a different kind of comparison between classics and folklore, thus opening the road towards new interpretations.